A new species of Gladiolus from Southeastern Türkiye, Gladiolus siirtensis (Iridaceae, Crocoideae) - Pinar, Süleyman Mesut; Eroğlu, Hüseyi̇n; Fi̇dan, Mehmet (Phytotaxa, 2023)
Gladiolus siirtensis (Iridaceae) is described as a new species from the Pervari district, Siirt province in the southeast of Türkiye. Gladiolus siirtensis is similar to G. humilis, but it is easily distinguished by its shorter stem, oblong or oblanceolate first leaves, dense spike with secund flower arrangement, absence of fusiform blotch on the lower segments of perigone, shorter anthers, style and stigma lobes and obovoid capsule. A detailed morphological study, including pollen and seed surface characteristics was undertaken for the new species. A complete morphological and palynological description is provided, including distribution data of the new species and related ones.